Pengembangan Sistem Informasi Pemesanan dan Reservasi Berbasis Web pada Kafe Teras House - Caca Arif Herdian; Maya Destriani; Tazkia Salsabila Ardan; Zaini Dahlan; Iqbal Rizki Maulana; Raihan Saputra (FAKULTAS ILMU KOMPUTER, 2026)
Teras House faced operational constraints due to conventional transaction and reservation systems, such as overlapping table schedules and slow financial recapitulation. This study aimed to develop a fully integrated web based menu ordering and table reservation information system. The novelty of this system lay in its adaptation to the unique characteristics of a third-place business model that combined culinary activities and room facility management. The methodology employed was the system development life cycle, which encompassed requirement analysis, object-oriented modeling, interface design, coding, and functional testing. The results indicated that the system integration successfully resolved operational bottlenecks and automated revenue recapitulation. Through black-box testing conducted on nineteen functional requirement specification items, all features were declared successful and valid without any system failures.